Plastic Waste Recycling Innovation as a P5-PPRA Activity at MI Miftahul Ulum Gumayun - Lyswidia Andriarsih; Abdul Aziz Syarif; Alvinaya Crisane Azzahrah; Ina Setiani; Muklas Zaenal Muttaqin; Risqotul Khalalia; Sofi Eka Lestari; Triana Yogi Rahmawati; Wafal Hana (Prodi PGMI STIT Sunan Giri Bima, 2026)
The problem faced around MI Miftahul Ulum Gumayun is the high amount of plastic waste that has not been managed properly. For this reason, an innovation in recycling plastic waste was carried out and made it a P5-PPRA activity. This study aims to observe how the innovation of recycling plastic waste as a P5-PPRA activity at MI Miftahul Ulum Gumayun. This research was conducted at MI Miftahul Ulum Gumayun by involving representatives of 6th grade students consisting of four boys and four girls. Data collection through observation and documentation. For data analysis, the stages of data reduction, data presentation, and conclusion drawing were carried out. The results of this study are that the innovation of recycling plastic waste as a P5-PPRA activity is one form of effective empowerment in waste management. In addition to being a P5-PPRA activity, the product of this plastic waste recycling innovation was also displayed at the Annual Jamboree Carnival event. And MI Miftahul Ulum Gumayun won 1st place in the Best Carnival at the 2025 Jamboree. With this research, it is hoped that awareness about waste management and the importance of protecting the environment will increase so that students can be more creative in processing waste.